2017
DOI: 10.1021/acs.est.6b06252
|View full text |Cite
|
Sign up to set email alerts
|

Indoor/Outdoor Relationships and Anthropogenic Elemental Signatures in Airborne PM2.5 at a High School: Impacts of Petroleum Refining Emissions on Lanthanoid Enrichment

Abstract: Outdoor emissions of primary fine particles and their contributions to indoor air quality deterioration were examined by collecting PM inside and outside a mechanically ventilated high school in the ultraindustrialized ship channel region of Houston, TX over a 2-month period. By characterizing 47 elements including lanthanoids (rare earth elements), using inductively coupled plasma-mass spectrometry, we captured indoor signatures of outdoor episodic emissions arising from nonroutine operations of petroleum ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 62 publications
3
5
1
Order By: Relevance
“…Our indoor and outdoor PM 2.5 mass concentration results are similar to those of previous studies [70][71][72], which also found that the outdoor mass concentration was greater than the indoor concentration. Studies by Martuzevicius et al [73] and Abdel-Salam [74] found a significant correlation between the distance from major traffic roads and outdoor PM 2.5 mass concentrations in residential areas.…”
Section: Indoor and Outdoor Pm 25 Mass Concentrationsupporting
confidence: 91%
See 1 more Smart Citation
“…Our indoor and outdoor PM 2.5 mass concentration results are similar to those of previous studies [70][71][72], which also found that the outdoor mass concentration was greater than the indoor concentration. Studies by Martuzevicius et al [73] and Abdel-Salam [74] found a significant correlation between the distance from major traffic roads and outdoor PM 2.5 mass concentrations in residential areas.…”
Section: Indoor and Outdoor Pm 25 Mass Concentrationsupporting
confidence: 91%
“…The positive correlation between indoor and outdoor PM 2.5 concentrations, R-square values close to one, and the corresponding I/O ratios of less than one, confirm that indoor concentrations were influenced by PM 2.5 from the outdoor environment. Similar results were reported by Massey et al [77] and Bozlaker et al [72], who also found a strong and positive relationship between indoor and outdoor PM 2.5 mass concentrations. The results are expected because it has been reported that approximately 35-70% of indoor PM 2.5 comes from the outdoor environment [64,78].…”
Section: Relationship Between Indoor and Outdoor Pm 25 Mass Concentrationssupporting
confidence: 90%
“…We were able to examine the impact of some of these factors using a generalized linear model with one-year field data. The outdoor PNC was found to be the most important predictor of indoor PNC at all meteorological conditions [30,35], but the residents' preferences and activities may dominate the IOR when considerable indoor activities prevail, e.g., smoking, stir and fry cooking, vacuum cleaning, dusting, etc. While smoking and cooking tend to elevate the fine PNC, house holding activities affect to a larger extent the coarse fraction [20,36].Information about the indoor-to-outdoor ratio (IOR) of particle concentrations in different regions and seasons may help epidemiologists and policy makers understand the health effects of ambient air pollution and correct their exposure assessments with a measure that represents indoor exposure as well.…”
Section: Discussionmentioning
confidence: 96%
“…Metals that loaded on Factor 2 (Al, V, Cr, and Co) might be associated with either industrial or natural sources. Although Al, V, and Cr from crustal materials are naturally present in soil, these elements are also emitted from petrochemical plants and refineries, from burning heavy oil for shipping vessels, and from other metal-related industrial facilities (Moreno et al 2010;Bozlaker et al 2017;Han et al 2017), which are abundant in the greater Houston area (US EPA 2019). Factor 3 (Ni, Cu, Zn, and Se) consisted of metals that may be associated with traffic sources such as vehicular and railroad emissions (e.g., break wear) (Harrison et al 2012;Ha et al 2014).…”
Section: Discussionmentioning
confidence: 99%